Heat transfer analysis of solar-thermal dissociation of NiFe2O4 by coupling MCRTM and FVM method. (December 2015) - Huang, Xing; Chen, Xiang; Shuai, Yong; Yuan, Yuan; Zhang, Tong; Li, Bingxi; Tan, Heping
Highlights: Radiative properties of NiFe2 O4 particles are obtained by experimental and numerical method. A heat transfer model suitable for thermal dissociation process of NiFe2 O4 is developed. Conversion rate and temperature field inside the proposed solar reactor are investigated at different operating parameters. Abstract: NiFe2 O4 is a promising candidate that used in solar thermochemical hydrogen production due to its better redox performance. The solar-thermal dissociation processes of NiFe2 O4 are analyzed by the Monte Carlo Ray Tracing Method (MCRTM) and Finite Volume Method (FVM), taking into account the conduction, convection, radiation and chemical reaction. More, the chemical co-precipitation method is employed to synthesize nanoscale NiFe2 O4 and combine experimental and numerical method to determine its radiative properties. The metallic oxide dissociation solution obtained from the MCRTM and the FVM is compared with that from other methods in order to validate the MCRTM and the FVM for heat transfer analysis of solar-thermal dissociation. Finally, parametrical studies using the method are used to provide advices for structural designs of a new proposed solar reactor. The results can provide useful application for improving the efficiency of conversion from solar energy to chemical energy in the future.